Approved budget: 2005 Vol.II - Federal Republic of Nigeria (Lagos : The federal government press, 2005)
This book is the 2005 fiscal year approved budget of the federal government of Nigeria.
Title from cover: 2005 fiscal year
asm; 23/01/2019
Arch
Keywords: Budget; Nigeria